2021
DOI: 10.24042/febi.v6i1.9014
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the Covid-19 Pandemic on the Financial Performance of Sharia Commercial Banks: an Empirical Evidence from Indonesia

Abstract: The Covid-19 pandemic has substantially changed the world. Social, economic, culture as well political landscapes have been forced to adapt to a new normal—a previously unfamiliar or atypical situation that has become standard, usual, or expected. This has, to some degree, obstructed economic activity throughout many sectors, with important aftermaths for businesses and households. Companies that have stopped operating will lose revenue, and, therefore, may not be able to repay the loan. Equally, households wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 0 publications
1
10
1
1
Order By: Relevance
“…It shows that the Covid-19 Pandemic in Indonesia has had no impact on the ability of Islamic banks to manage non-performing financing. These results are consistent with the research of (Sutrisno et al, 2020); (Azmi et al, 2021); (Siswantoro, 2022); Utami and Makhrus (2022);and Sugiharto et al (2021), who also found that there was no difference in the NPF ratio before and during the Covid-19 Pandemic. However, this result opposes Rifqi & Condro (Muhammad & Triharyono, 2019), who found a difference in NPF before, during, and after the global financial crisis of 2008.…”
Section: Credit Risksupporting
confidence: 92%
See 2 more Smart Citations
“…It shows that the Covid-19 Pandemic in Indonesia has had no impact on the ability of Islamic banks to manage non-performing financing. These results are consistent with the research of (Sutrisno et al, 2020); (Azmi et al, 2021); (Siswantoro, 2022); Utami and Makhrus (2022);and Sugiharto et al (2021), who also found that there was no difference in the NPF ratio before and during the Covid-19 Pandemic. However, this result opposes Rifqi & Condro (Muhammad & Triharyono, 2019), who found a difference in NPF before, during, and after the global financial crisis of 2008.…”
Section: Credit Risksupporting
confidence: 92%
“…This result is consistent with several previous studies, i.e., by Sutrisno et al (2020), Siswantoro (2022), and Utami and Makhrus (2022), for the ROA ratio. However, the NOM ratio of these results is inconsistent with several studies, Sutrisno et al (2020);and Sugiharto et al (2021). It is due to the extended study period, and in 2021 economic conditions in Indonesia have begun to return to stability.…”
Section: Profitabilitycontrasting
confidence: 58%
See 1 more Smart Citation
“…Being priority customers, the withdrawals greatly impacted the IRBs. However, in some areas, the virus had minor effects on the performance of Capital Financing (Mansour et al, 2021;Sugiharto et al, 2021) due to the variation between regions in their economic strength and the effectiveness of the authorities in implementing social restrictions (Hill et al, 2008;Roziqin et al, 2021;Sevindik et al, 2021;Vidyattama, 2013). The resilience of Capital Financing during the pandemic was mainly attributed the IRBs' orientation to profit and loss sharing and strict supervision in the financing process (Omar, 2020;Rabbani et al, 2021).…”
Section: Resultsmentioning
confidence: 99%
“…It can be seen from the increase in financial ratios such as CAR and ROA. (Pradesyah & Putri, 2021), (Sugiharto et al, 2021), (Afandi, 2021) and (Fakhri & Darmawan, 2021) also use financial ratios in measuring the performance of Islamic banks.…”
Section: Introductionmentioning
confidence: 99%